On Applying Document Similarity Measures for Template based Clustering of Web Documents - Bagban, TI; Kulkarni, PJ (International Journal of Computer Sciences and Engineering, 2025)
World Wide Web is the useful and easy way to get the source of information on the Internet. In order to reduce the content generation and publishing time, templates are used to populate the contents in web documents. Template provides easy access to the web document contents through their layout and structures. However, for search engines, due to its irrelevant terms, the templates degrade search engines accuracy and performance. Also the templates are used by wrapper induction tools used in information extractor to extract and integrate information from various E-commerce sites. Thus it has received a lot of attention to improve the search engines performance and content integration. In this paper we have discussed how heterogeneous web documents i.e. web documents generated from different templates, can be clustered. We have applied document similarity measures to cluster the heterogeneous web documents generated from templates. Our experimental results on real data sets show that cosine distance similarity measure is more suitable for template based clustering of heterogeneous web documents.